PARTICIPATION OF KAZAKHSTAN IN DISPUTES IN THE FRAMEWORK OF WTO AS A THIRD PARTY - Tleubekov, Султан Торебекович; Aidarbayev, Сагынгалий Жоламанович; Palao Moreno, Гильермо (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article is devoted to the analysis of the experience of participation of the Republic of Kazakhstan in disputes within the WTO as a third party. The dispute settlement system is regarded by the World Trade Organization as the central pillar of the multilateral trading system. One feature of the WTO’s dispute settlement mechanism is the right of member states to participate in trade proceedings as a third party. The relevance of the research topic is due to the importance of summing up the results of Kazakhstan’s activities, for six and a half years since its accession, in the procedures for resolving disputes within the WTO. The article deals with 35 WTO disputes in which Kazakhstan took part as a third party. The authors note that 20 disputes were related to customs and tariff regulation measures, and 15 disputes were related to non-tariff regulation measures. Only in two disputes out of 35, Kazakhstan expressed its position regarding the proceedings, despite this, each dispute has its own practical significance. Particular attention is paid to the conclusions on disputes in relation to the Republic of Kazakhstan. Also, the article discusses the reasons and significance of participation in WTO disputes as a third party. The results of the study show that the disputes mainly concerned the application of trade remedies, namely anti-dumping and countervailing duties, and special protective measures. In this regard, this article proposes to pay attention to other measures of non-tariff regulation of international trade, in particular, to sanitary and phytosanitary measures.